Couple relationships among parents of children and adolescents with Autism Spectrum Disorder: Findings from a scoping review of the literature. (September 2015) - Saini, Michael; Stoddart, Kevin P.; Gibson, Margaret; Morris, Rae; Barrett, Deborah; Muskat, Barbara; Nicholas, David; Rampton, Glenn; Zwaigenbaum, Lonnie
Highlights: Longstanding gap in evidence about relationships among parents of children with ASD. Scoping review highlights the importance of considering couple relationships. Limited data suggests that divorce rates are lower than commonly perceived. Results highlight a variety of factors related to couples' distress. Further emphasis needs to consider access to services and supports. Abstract: To explore commonly-held assumptions regarding the risk of couple breakdown in families of children with Autism Spectrum Disorder (ASD), a scoping review of quantitative ( n  = 39), qualitative ( n  = 15), and mixed ( n  = 5) studies was conducted. Findings include themes related to marriage and divorce rates, relationship satisfaction and conflict, and other significant variables. Parents and service providers of individuals with ASD will benefit from knowing that strategies such as developing common goals, increasing partner respect, securing social support, reducing stress, and instilling hope are all factors which support the development and maintenance of positive couple and co-parenting relationships.